Penilaian Risiko Kepatuhan Perusahaan Pelayaran terhadap Peraturan dan Standar Inaportnet (Studi Kasus di PT. Meratus Surabaya) - Tini Utami; M. Aji Luhur Pambudi; Miftahul Huda (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2025)
Operational risk management is a crucial element in ensuring the effectiveness of port logistics services, particularly with the advent of digitalization in port operations. The Inaportnet agents at PT Meratus Surabaya, who serve as key intermediaries in the port administrative process, face several operational risks that impact the company, especially those related to data entry errors in the Inaportnet system and the mitigation strategies applied. This study was conducted with the aim of comprehensively evaluating the level of compliance of Inaportnet agents at PT Meratus Surabaya with the applicable operational risk management standards. In addition, the research seeks to identify and analyze the various strategies implemented by the company to maintain operational effectiveness and ensure the continuity of its logistics services. Using a qualitative case study approach, data were collected through interviews, observations, and internal documentation. The analysis results indicate that data entry errors significantly contribute to delays in document validation and overall logistics services. Therefore, systematic measures such as digitalizing procedures, staff training, and strengthening inter-agency coordination are required to enhance operational resilience and the company's competitive advantage. Accordingly, this study is expected to provide deeper insights into risk management practices within the company's operational environment and their contribution to the stability and sustainability of PT Meratus's logistics business.